GINGIVECTOMY AS A CROWN LENGTHENING PROCEDURE FOR ALTERED PASSIVE ERUPTION TREATMENT - Wildhan Septianda Bhakti; Agung Krismariono (FKG Unlam, 2020)
ABSTRACTBackground: Altered passive eruption is a condition that can make clinical crown of teeth seems shorten. The excessive gum or dentogingival junction level that overlap to enamel become causal factor for altered passive eruption. Crown lengthening is one of treatment that can treat altered passive eruption. One of crown lengthening procedure is gingivectomy. Purpose: To correct excessive gingiva and achieve ideal teeth appearance by using gingivectomy as crown lengthening procedure. Case: A 21‑years‑old, systemically healthy, non‑smoking female, referred from orthodontist to treat patient’s overlap gingiva. From the patient’s point of view, her upper front teeth were unpleasant to see. There were no abnormalities in extraoral. Intraoral, there were upper front clinical crown of teeth that seem shorter. Case management: The treatment started from administration of anesthetic agent, application of pocket marker forceps, gingival cutting and trimming process, then periodontal pack application. Treatment results were quite good. The appearance of upper front teeth became ideal in width and length ratio. Conclusion: Gingivectomy is one of crown lengthening method that can solve excessive gingiva in altered passive eruption.Keywords: Altered passive eruption; Crown lengthening; Dentogingival junction; Gingivectomy